The archaeology of island colonization (Gainesville)
xv, 377 sayfa
Keywords: “This volume details how new theories and methods have recently advanced the archaeological study of initial human colonization of islands around the world, including in the southwest Pacific, the Mediterranean, the Caribbean, and Southeast Asia.“ --